The Alteration of SNAIL2 and MMP-9 Protein Expression of JEG-3 Choriocarcinoma Cell by Methanolic Extract of Tamarindus Indica Fruit - Candra Rini Hasanah Putri; Sutiman Bambang Sumitro; Setyawati Soeharto; Karyono MIntaroem (Journal of Global Pharma Technology, 2019)
Objective: Tamarindus indica is one of the famous natural plant that has various effects on health. Recent research has begun to examine the effect of Tamarindus indica on cell malignancy. One of the things that happens in cell malignancy is an increasing ability of cell migration, which is characterized by increasing expression of Snail2 and MMP-9. This study was conducted to determine the effect of extract of Tamarindus indica Fruit Extract (TIFE) towards Snail2 and MMP-9 expression in JEG-3 cells.Methods :.TIFE were extracted by using methanol. JEG-3 cells were grown in culture medium treated with TIFE (at 0, 25, 50 and 100 µg/ml). Immunofluorescence staining was carried out, and observed under Confocal Laser Scanning Microscope.Result: Snail2 expression after treatment with TIFE 50 and 100 µg/ml higher than control- (P=0.015 ; P=0.001) whereas at MMP-9 expression there was a biphasic pattern, in which the MMP-9 expression peaked at concentration of 50 µg/ml (P=0.002), then MMP-9 expression decreased at 100 µg/ml concentration. Conclusion : The expression of Snail2 influence MMP-2 expression after treat with TIFE, so it might increase the potential for JEG-3 cell migration Keywords : Methanolic extract, Tamarindus indica, Snail2, MMP-9